EFFECT OF DIFFERENT ADMINISTRATION METHODS OF VITAMIN AD3E TO HATCHING EGGS AND SUPPLEMENT IT WITH DRINKING WATER ON HATCHABILITY TRAITS AND POST HATCH PERFORMANCE AND BIOCHEMICAL PARAMETER OF BROILER - Hassan, W. H.; Tayeb, I. T. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2021)
This study was conducted at the Badi Hatchery and poultry house / department of animal production / College of Agriculture engineering science/ University of Duhok. The aim of study was to investigate the effect of different administration methods of vitamin AD3E to hatching eggs on hatchability and post hatch productive performance and some physiological parameter of broiler. A total of one thousand and two hundred fifty (1250) hatched eggs were distributed into five groups each groups 250 eggs. The experimental treatments were as the follow: T1 (Control), T2 (sham control)(injected with 0.1 ml normal saline), T3 (injected with 0.1 ml of vitamin AD3E dissolved in 5 ml of vitamin in 1 ml of water) T4 (Spraying vitamin AD3E 1 ml /L water), T5 (Dipping vitamin AD3E 1 ml /L water). During the rearing period, each treatment divided into 2 group of replications, (5 replication) for each group that is from one treatment exactly. First 5 five replications (R1-R5) for each treatment given different doses of vitamin at different rearing age via drinking water and other 5 five replications (R6-R10) were drink normal water throughout the rearing period which is at least 5 weeks. Weekly Live body weight, body weight gain, feed consumption, feed conversion ratio, mortality percentage, Production index were recorded, (Total protein, glucose and cholesterol), blood serum titer for testing the immunity of chicken against diseases Newcastle (ND) and Gumboro, infectious bronchitis (IB). The overall data shows the following results: - In hatching stage there were significant affect in chick weight and chick to egg ratio and in rearing stage live body weight, body weight gain, feed conversion ratio, production index, serum glucose, Newcastle Gambaro and infectious bronchitis disease.